Measuring stress in medical education: validation of the Korean version of the higher education stress inventory with medical students. Issue 1 (December 2016) - Shim, Eun-Jung; Jeon, Hong; Kim, Hana; Lee, Kwang-Min; Jung, Dooyoung; Noh, Hae-Lim; Roh, Myoung-Sun; Hahm, Bong-Jin
Abstract Background Medical students face a variety of stressors associated with their education; if not promptly identified and adequately dealt with, it may bring about several negative consequences in terms of mental health and academic performance. This study examined psychometric properties of the Korean version of the Higher Education Stress Inventory (K-HESI). Methods The reliability and validity of the K-HESI were examined in a large scale multi-site survey involving 7110 medical students. The K-HESI, Beck Depression Inventory (BDI) and questions regarding quality of life (QOL) and self-rated physical health (SPH) were administered. Results Exploratory factor analysis of the K-HESI identified seven factors: Low commitment; financial concerns; teacher-student relationship; worries about future profession; non-supportive climate; workload; and dissatisfaction with education. A subsequent confirmatory factor analysis supported the 7-factor model. Internal consistency of the K-HESI was satisfactory (Cronbach's α = .78). Convergent validity was demonstrated by its positive association with the BDI. Known group validity was supported by the K-HESI's ability to detect significant differences on the overall and subscale scores of K-HESI according to different levels of QOL and SPH. Conclusions The K-HESI is a psychometrically valid tool that comprehensively assesses various relevant stressors related to medical education. Evidence-based stress management in medical education empirically guided by the regular assessment of stress using reliable and valid measure is warranted.